Protective effect of piper longum methanolic extract on alcohol induced intoxication model in rats - KONDA RAVI KUMAR; A. PRATHYUSHA (International Journal of Pharma and Bio Sciences, 2019)
Long pepper has its reference from the ancient textbooks of Ayurveda. Ayurveda has explained various uses of long pepper for dietary purpose as well as for various health purposes. The present investigation carried out on methanolic extract of Piper Longum for in vitro antioxidant activity and hepatoprotective activity against alcohol induced hepatotoxicity in Wistar rats. The in vitro antioxidant activity of Long Pepper was screened by superoxide, hydroxyl, lipid peroxide and DPPH radical scavenging activity. The various antioxidant activities were correlated with ascorbic acid as a standard. Hepatotoxicity was induced in rats by oral administration of 40% ethanol for 25 days. The protective activity of methanolic extract of Long Pepper against the alcohol induced liver damage was investigated at selected dose of 100, 200, 400 mg/kg body weight. In the superoxide, hydroxyl, lipid peroxide and DPPH radical scavenging activity, the IC50 values of Piper Longum extract were 265.79, 430.89, 608.44 and 338.59 µg/ml respectively. The level of serum hepatic biomarkers Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatase (ALP) and Total bilirubin (TB)), physical parameters (liver weight and volume) and antioxidant enzymes (superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT)) were determined to assay hepatotoxicity. Elevated serum liver biomarkers (AST, ALT, ALP and total bilirubin), physical parameters and antioxidant enzyme levels were caused by ethanol administration as evidenced hepatic damage in rats. The toxic effect of ethanol on the above parameters in curative models was prevented by the administration of Piper Longum and Silymarin. Conclusion was arrived that methanolic extract of Piper Longum have significant hepatoprotective and antioxidant activity against ethanol induced hepatotoxicity.